Imperialism, racial capitalism, and postcolonialism - Callinicos, Alex (Southernising criminology, 2024)
The postcolonial has ceased to be an academic category (if it ever was such) and has become a stake in the ‘culture war’ in Western liberal democracies over their relationship to their past and present histories of oppression. One increasingly widely used concept in the critical interrogation of these histories is that of racial capitalism. It seems to have been coined during the 1970s by South African Marxists seeking to understand the relationship between apartheid and capitalism. Now the concept of racial capitalism is being increasingly universalised, with the inevitable risk that it is also essentialised. I shall probe the issues involved, partly by returning to the concept’s origins and partly by seeing how much setting them in the context of the Marxist theory of imperialism helps to clarify the relationship between global capitalism and racial oppression.